Ethnicity, Separatists Agitations and National Stability in Nigeria: A Study of the South East Geo-Political Zone (1999 – 2020) - Ayomola, Oluranti; Oketokun, Olalekan (NIU Journal of Social Sciences, 2021)
The issue of national stability in Nigeria has become one of great concern both locally and internationally, this is because, since the beginning of the present fourth republic in 1999, the nation has been gripped by all sorts of crises which have threatened her existence. The resurgent separatist agitations by the mainly Igbo ethnic group of the South east geo-political zone has been a major crisis that has caused so many deaths, casualties and loss of property and despite the various measures taken by the Federal government including proscription of IPOB and designating the separatist group a terrorist organisation, the agitations has persisted and refused to abate.  This study, therefore, is undertaken to unravel the motivations for the renewed separatist agitations and its implication on national stability amongst others. The study adopted the phenomenology research design and relied on qualitative data, with the interview guide as research instrument. Data were also sought from previous works on the subject in books, journals, newspapers, periodicals and other internet based sources and were content analysed. The population of the study are the people of the 5 states in the south east geo-political zone, with respondents from Imo and Abia States as the sample population. The study found out that the renewed agitations were as a result of the feeling of marginalisation of the Igbo people of South east zone by successive administrations since 1999. The study therefore, recommends that the issue of marginalisation should be addressed by the federal government, the equitable allocation of resources to all the geo-political zones should be prioritised by the government, that the option of dialogue with the agitators should be explored and the federal government should eschew the use of force and military strategy being used for now. Above all, referendum should be conducted to know the true feelings of the people in respect of the issue amongst others. Keywords: Ethnicity, Separatist, Agitations, National stability, South east, Nigeria